2018
DOI: 10.1371/journal.pone.0197359
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity and antioxidant activities of culturable fungal endophytes associated with the mangrove species Rhizophora stylosa and R. mucronata in the South China Sea

Abstract: Mangrove endophytic fungi can produce impressive quantities of metabolites with promising antioxidant activities that may be useful to humans as novel physiological agents. In this study, we investigated the phylogenetic diversity and antioxidant potential of 46 fungal endophytes derived from the mangrove species Rhizophora stylosa and R. mucronata from the South China Sea. The fungal isolates were identified using a combination of morphological characteristics and phylogenetic analysis of the internal transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 48 publications
1
41
0
1
Order By: Relevance
“…Some studies have also showed that endophytes can increase the survival rate of host plants during flooding stress by producing antioxidants independently [31,32]. Severe oxidative damage of free radicals has been confirmed to be associated with various diseases, including cancer, inflammation, aging and neurodegenerative diseases [33]. Thus, antioxidants should be warranted in the enhancement of human health [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also showed that endophytes can increase the survival rate of host plants during flooding stress by producing antioxidants independently [31,32]. Severe oxidative damage of free radicals has been confirmed to be associated with various diseases, including cancer, inflammation, aging and neurodegenerative diseases [33]. Thus, antioxidants should be warranted in the enhancement of human health [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Following standard procedures [ 26 ], endophytic fungi were isolated from fresh, healthy hypocotyls of Ceriops tagal (Rhizophoraceae), which were collected in October 2015 in Dong Zhai Gang-Mangrove Garden on Hainan Island, China. The fungus (strain no.…”
Section: Methodsmentioning
confidence: 99%
“…These known compounds from mangrove plant endophytes include terpenes, chromones, coumarins, polyketides, alkaloids, and peptides (Kui-Wu et al, 2014;Xu, 2015;Ancheeva et al, 2018). These compounds exhibit a broad spectrum of biological properties such as antioxidant, cytotoxic, antifungal, antibacterial, α-glucosidase, acetylcholinesterase, antivirus (Kui-Wu et al, 2014;Xu, 2015;Ancheeva et al, 2018;Zhou et al, 2018;Manganyi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%